Integrasi Nilai Tri Kaya Parisudha dan Karma Phala sebagai Moderasi Pengaruh Komitmen Profesional dan Pengalaman terhadap Perilaku Etis Auditor - Wiguna, I Gd Nandra Hary; Nyoman Ayu Wulan Trisna Dewi (Universitas Pendidikan Ganesha, 2024)
This study aims to examine the effect of professional commitment and auditor experience on auditors’ ethical behavior, with Tri Kaya Parisudha and Karma Phala serving as moderating variables. The research is motivated by the importance of ethical values and spirituality in the auditing profession, particularly in Bali, where strong local wisdom plays a central role in societal and professional life. A quantitative research approach was employed, using a survey method with questionnaires distributed to 85 auditors working at Public Accounting Firms in Bali Province. Data were analyzed using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS) method with the SmartPLS software. The findings reveal that professional commitment and auditor experience have a positive and significant influence on auditors’ ethical behavior. This indicates that auditors with high professional commitment and sufficient experience tend to exhibit more ethical conduct in performing their duties. However, the results also show that Tri Kaya Parisudha and Karma Phala do not have a significant moderating effect on the relationships between professional commitment or experience and ethical behavior. These findings suggest that although local cultural values possess strong philosophical meanings, their application in the professional context requires more contextual and practical approaches. This study contributes to the literature on auditors’ ethical behavior by integrating professional factors with local cultural wisdom. The practical implications emphasize the need to strengthen professional commitment, enhance auditor experience, and develop strategies to internalize local cultural values into professional ethics education and training.